The effect of green brand image on green brand equity through the green consumer satisfaction: The case for organic food products in Ho Chi Minh City - Mai, Xuan Dao; Trinh, Minh Man; Ngo, Thien Nhi; La, Gia Phung; Le, Yen Tam; Nguyen, Phuong Thuy (Journal of Finance - Marketing Research, 2025)
This paper examines the effect of green brand image on green brand equity through green consumer satisfaction. Based on survey data collected from 323 consumers of organic food products in Ho Chi Minh City, this research adopts a mixed-method approach, combining both qualitative and quantitative methods. Smart-PLS software was used to analyze the data. The results show a positive direct effect of green brand image on green brand equity, as well as a mediating effect of green consumer satisfaction on the relationship between green brand image and green brand equity for organic food products. Additionally, the results indicate that there are no significant differences in the relationship in the research model based on gender. However, there are differences based on occupation, and partial differences exist in all relationships based on age, residence location, and salary. Based on these results, several research implications are suggested for organic food businesses, state agencies, and consumers to enhance green brand equity for organic food products and encourage consumers to increase their consumption of organic food.